Soil amendments improve growth and survival of grey mangroves in arid sabkha, Saudi Arabia - Dhawi, Faten; Ghafoor, Abdul; Al Dossary, Othman; Alsubaie, Bader; Zarban, Randa A.; Alomair, Gadir; Alkhaldi, Nora Abdullah; Abrogueña, Jeff Bogart R.; Campbell, Calum (Frontiers in Environmental Science, 2026)
Mangrove ecosystems are globally recognized as potent natural climate solutions due to their exceptional potential for carbon sequestration. Yet, they are rapidly declining under mounting anthropogenic pressures such as coastal urbanization, sea-level rise, and habitat conversion. This study investigates the viability of establishing Avicennia marina (grey mangrove) in an arid sandflat (known as sabkha) at two contrasting locations - Qurayyah and Rahimah - in the Eastern Province of Saudi Arabia. The main objective of this study was to compare the survival rate of A. marina mangrove seedlings between five soil amendments, namely, control, peat moss, Multi-microbial consortium (MMC) fertilizer and red soil. Results showed that peat moss, included for its high moisture retention and nutrient provisioning capacity, consistently achieved higher survival rates at both sites. In addition, peat moss consistently improved seedling survival at both sites. Multi-microbial consortium is recognized for its role in enhancing plant tolerance to salinity and facilitating nutrient uptake, particularly under nutrient-poor and saline conditions such as sabkha soils. In this study, Multi-microbial consortium -treated seedlings demonstrated notable improvements in nitrogen assimilation and chlorophyll content, highlighting the symbiont’s contribution to enhancing physiological resilience under environmental stress. Notably Rahimah showed overall better survival outcomes than Qurayyah, likely due to its proximity to tidal waters. These findings indicate that the combination of appropriate soil amendments and closeness of sabkha to coastal waters is critical for improving mangrove survival in such environments. Overall, integrating targeted soil amendments with strategic site selection and optimized hydrological conditions could substantially enhance mangrove establishment, supporting climate-adaptive restoration in arid, hypersaline coastal systems.